Cichorium pumilum Jacq Extract Inhibits LPS-Induced Inflammation via MAPK Signaling Pathway and Protects Rats From Hepatic Fibrosis Caused by Abnormalities in the Gut-Liver Axis - Han, Chang; Wu, Xi; Zou, Nan; Zhang, Yunsheng; Yuan, Jinqi; Gao, Yuefeng; Chen, Wen; Yao, Jia; Li, Cong; Hou, Jinqiu; Qin, Dongmei (Frontiers in Pharmacology, 2021)
The development of liver fibrosis is closely related to the gut microbiota, and the "gut-liver axis" is the most important connection between the two. Ethyl Acetate Extract of Cichorium pumilum Jacq (CGEA) is an herbal extract consisting mainly of sesquiterpenoids. The anti-inflammatory and hepatoprotective effects of CGEA have been reported, but the anti-fibrotic effects of CGEA via intestinal microbes and the "gut-liver axis" cycle have rarely been reported. In this study, we observed that CGEA not only directly attenuated inflammatory factor levels in inflamed mice, but also attenuated liver inflammation as well as liver fibrosis degeneration in rats with liver fibrosis caused by colitis. We observed in vitro that CGEA significantly promoted the growth of Bifidobacterium adolescentis. Similarly, fecal 16S rDNA sequencing of liver fibrosis rats showed that CGEA intervention significantly altered the composition of the intestinal microbiota of liver fibrosis rats. CGEA increased the abundance of intestinal microbiota, specifically, CGEA increased the ratio of Firmicutes to Bacteroidetes, CGEA could significantly increase the levels of Ruminococcus. In addition, CGEA intervention significantly protected intestinal mucosal tissues and improved intestinal barrier function in rats.Lactucin is the main sesquiterpenoid in CGEA, and HPLC results showed its content in CGEA was up to 6%. Lactucin has been reported to have significant anti-inflammatory activity, and in this study, we found that Lactucin decreased p38 kinases (p38), phosphorylation of the extracellular signal-regulated kinase (ERK) and protein kinase B (AKT) protein phosphorylation in lipopolysaccharide (LPS)-activated RAW264.7 cells, thereby reducing mRNA expression and protein expression of pro-inflammatory factors inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), and inhibiting the release of inflammatory factors interleukin (IL)-6 and nitric oxide (NO), exerting anti-inflammatory effects. In summary, the prevention of liver fibrosis caused by intestinal inflammation by CGEA may be achieved by regulating the intestinal microbiota and restoring the intestinal barrier thereby improving the "gut-liver axis" circulation, reducing liver inflammation, and ultimately alleviating liver fibrosis. Notably, the direct anti-inflammatory effect of CGEA may be due to its content of Lactucin, which can exert anti-inflammatory effects by inhibiting the phosphorylation of Mitogen-activated protein kinase (MAPK) and Akt signaling pathways.